A probabilistic study on the mixed-mode fracture in functionally graded materials. (February 2021) - Pan, Haizhu; Song, Tianshu; Ge, Haimiao
Highlights: A probabilistic fracture problem of FGMs with an slant crack was investigated. Effects of the random micro-structure on material properties and SIFs were discussed. Randomness in micro-structure of FGMs may have more influence on the larger crack. Abstract: This article reports the results of a probabilistic study on the mixed-mode fracture problem of an internal slant crack in a functionally graded material strip. The study involves randomness description of the micro-structural attributes of functionally graded materials; the effects of the random micro-structural attributes on the macroscopic properties of functionally graded materials; analytical solutions of mode-I and mode-II stress intensity factors and analysis of its probabilistic characteristics. The influences of the randomness in micro-structural component on the statistics (e.g. the mean, the standard deviation) of the shear modulus of functionally graded materials are graphically represented. The results also reveal this research may be more meaningful on the probabilistic characteristic of stress intensity factors of functionally graded materials with the larger size slant crack.